Business Strategy and Sales Performance on Plant-Based Restaurant: An Exploration of Mediating Variable - Situmorang, Bornok; Soewarno, Noorlailie; ., Hamidah (Journal of Ecohumanism, 2024)
This research aims to explore variables that mediate the influence of business strategy on sales performance in Plant-Based Restaurants (PBR) and the results of exploration are tested empirically using a quantitative approach. The theory of business strategy underlies the conceptual framework between strategy, organizational agility and performance of plant-based restaurants. This research uses mixed research method. The qualitative study (Phase 1) using thematic analysis were followed by a quantitative study (Phase 2) using multiple linear analysis and path analysis. The results of Phase 1 are a conceptual framework and some hypotheses. The results of Phase 2 are conclusions that confirm the results of Phase 1. The overall results conclude that innovation strategy, marketing strategy and organizational agility significantly have a positive effect on sales performance, while low-cost strategies do not significantly have a positive effect on sales performance. In addition, organizational agility significantly mediates the influence of innovation and marketing strategies on sales performance. However, organizational agility only partially mediates the influence of low-cost strategy on sales performance. This research contributes to filling the gap in studies about plant-based foods and beverages connected to economics and business. This study explores the mediating variables between plant-based restaurants' strategy and sales performance.